Symptoms of eutrophication in intertidal macroalgal assemblages of Nuevo Gulf (Patagonia, Argentina) - Díaz, P. (2002)
The city of Puerto Madryn, located within a section of Nuevo Gulf (Patagonia, Argentina) known as Nueva Bay, can be regarded as an important centre of anthropogenic impact. Intertidal assemblages of macroalgae were studied in order to analyse whether eutrophication symptoms could be detected in the benthos. Three rocky shores showing similar characteristics were selected. One of these was located near the sewage outfall of the city of Puerto Madryn. Two control shores were chosen approximately 30 km northwards and southwards of the latter. Four seasonal surveys were performed between June 1998 and April 1999. Biomass data of 35 macroalgal species were analysed by diversity and evenness indices, non-Metric Multidimensional Scaling, and the ANOSIM permutation test. Species responsible for the differences between shores were identified by the SIMPER routine. The macroalgal assemblage of the impacted site was significantly different from those of the two control shores throughout the year. Ulva rigida, Corallina officinalis and Ralfsia sp. were the species mostly responsible for these differences. Results indicate that the impacted shore showed signs consistent with an intermediate degree of eutrophication, particularly the increased abundance of the opportunist green alga Ulva rigida.